O empreendedorismo e os itinerários formativos: estudo de uma proposta nas 1ªs séries do Ensino Médio - Ivo, Maurício Ceroni (2022)
The objective of this thesis is to analyze the pedagogical and curricular development of the Entrepreneurship program of the Business School.This study will be conducted through a High School project that takes place in the first two years of high school at Colégio Visconde de Porto Seguro. The status of the Brazilian education, especially high school education, requires curricular reform. Teachers frequently seek solutions and alternatives to enhance the curriculum. Given this scenario, it is important to put forward proposals and projects that are aligned with what is now called “The New Ensino Medio” – or The New High School. The Colégio Visconde de Porto Seguro has adapted its curricular structure, which has been put into practice for more than 20 years. The new curricular structure changed what was then named the Foreign Trade Technical program into The Entrepreneurship program of the Business School.This study focuses on the understanding of how this new pedagogical proposal aligns with both the new High School National Curriculum Guidelines and the Common Core Curriculum. The study will particularly emphasize the entrepreneurship structure present in the learning program. This thesis is based on research on projects and educational models from different countries, especially from the United States and Europe. The study analyzes examples and concepts aligned with the existent entrepreneurship learning proposals. It combines the technical concept and the possibilities of social entrepreneurship. The study of this combination is done through a case study. This case study will produce a comparative analysis that considers the school project, the syllabi, the programs, teachers’ meetings minutes, project videos, student orientation logs, and teaching plans approved by the school board. The curricular practice culminates in the final product developed by the students to the community through an entrepreneurship fair. This fair displays projects created and developed by the students such as business plans and strategies to insert and commercialize their products in international markets. All the projects follow the concepts learned in class, based on teachings of social and entrepreneurial responsibility. They are also aligned with the United Nations Sustainable Goals - 2030.According to the study, one can conclude that the proposal achieves the following pedagogical goals: deepening learning, strengthening full time learning, promoting universal values, developing abilities with autonomy, creativity, participation , and critique. It is possible to apply the concepts of this study in other schools, especially in public schools. However, these concepts must be adapted to each school’s reality